Analisis Risiko Banjir Sungai Tukad Unda Berbasis Pemodelan Hidrologi dan Hidraulika sebagai Dasar Strategi Mitigasi - I Made Alit Widnyana; Husnayaen Husnayaen; Suci Rahmawati (Jurnal Ilmiah Kanderang Tingang, 2026)
The Tukad Unda River in Klungkung Regency, Bali, plays a vital role in irrigation systems and local food security. However, land-use changes and increased rainfall intensity due to climate change and extreme weather events have heightened flood risks, potentially disrupting agricultural productivity and community accessibility. This study aims to develop a spatial flood vulnerability map of the Tukad Unda watershed using the 2D HEC-RAS hydrodynamic model integrated with Geographic Information System (GIS) data. Simulations were conducted for scenarios of extreme rainfall and land-use change, producing outputs such as water level, surface elevation, flow velocity, affected areas, and inundation distribution, validated through field data. The hydrological analysis shows that the design flood discharges for 50-year (Q50) and 100-year (Q100) return periods are 82.32 m³/s and 83.44 m³/s, respectively. Land use is dominated by mixed dryland agriculture with shrubs (39%), rice fields (20%), and dryland farming (14%). Based on HEC-RAS simulations, the difference in water depth and surface elevation between Q50 and Q100 conditions is relatively small (0.1–0.9 m), indicating that the hydraulic system of Tukad Unda remains stable but is approaching its maximum capacity. Therefore, flood mitigation strategies should focus on upstream conservation to control source discharge, optimizing river capacity in the middle segment to reduce inundation, and strengthening downstream protection systems to address the combined effects of river discharge and tidal influence.